KREDIBILITAS DAN OTENTISITAS GURU KEWIRAUSAHAAN TERHADAP KARAKTER KEWIRAUSAHAAN SISWA SMK NEGERI DI SURABAYA - Ghofur, Muhammad Abdul (UNIVERSITAS NEGERI SURABAYA, 2013)
Entrepreneurship in vocational education in Surabaya is still lack of attention. Many educators are paying less attention to character growth and entrepreneurial behavior. Their orientation is, generally only on preparing the workforce. To that end, the solution needs to be sought, how education can serve to turn people into human character or behavior and entrepreneurship. The research, therefore, aims at obtaining an explanation of the influence of teachers' entrepreneurship credibility and authenticity on the students entrepreneurial character in SMK Negeri Surabaya. This research is a verification. The technique used to test the hypothesis is structural equation model (SEM). The results provide an explanation that the variable credibility and authenticity of entrepreneurship teachers have simultaneous significant effect on students entrepreneurial character in SMK Negeri Surabaya, whereas the two variables are partially proven to be unsignificant.